A novel optical chip for affinity biosensors based on fluorescence anisotropy - Carloni, Adolfo (Cranfield University, 2008)
The subject of this thesis relates to the realisation of a novel biochip for sensors based on optical principles. In particular, affinity biosensors for antigens (IgG/anti-IgG), for a transcription factor, and for mRNA were studied and developed. The interrogation of the biosensors implied the development of a novel and innovative optical platform based on fluorescence which was designed, implemented and thoroughly characterised. The biosensors developed were integrated within an optical biochip connected to an innovative platform. The optical biochip was fabricated from polymethylmethacrylate (PMMA) formed by two pieces of PMMA complementary shaped in order to obtain four micro-channels. The lower part included the micro-channels and the inlet and outlet for the fluidic, while the sensing biolayer was immobilised on the upper part. The optical signal comprised the fluorescence emitted by the layer, which was anisotropically coupled to the cover and suitably guided by the chip. Several chemical treatments of the surface were investigated to obtain the most effective distribution of carboxylic groups for the covalent immobilisation of antibodies. Deposition of the polymers, in particular by Langmuir-Blodgett method, can enhance the performances of the chip going through lower detection limits. The potential of the optical chip as a biosensor was investigated in depth by means of a direct IgG/anti-IgG interaction carried out inside the flow channels. Following this, bioassays for the determination of the NF-kB transcription factor and for the mRNA that codifies for MGMT protein were implemented on the optical platform. The development and characterisation of the biosensors, the identification of the protocol for the bioassays and the design and characterisation of the optical platform were performed at the Institute of Physics Applied Carrara of National Research Council (IFAC-CNR), Firenze, Italy. The research devoted to the development of biosensing surfaces for the realisation of affinity biosensors able to detect and quantify antigens, transcription factors and RNA sequences were carried out at the laboratories of the Institute of Clinical Physiology of National Research Council (IFC-CNR), in Pisa, Italy. Langmuir-Blodgett deposition of polymers, Atomic Force Microscopy imaging and further fluorescence measurements of proteins covalently bound on the surfaces were performed at Cranfield University in Silsoe, England. The overall project starts from a first characterisation of the optical system, and comprehend the enhanced optimisation of the biochip performances until the realisation of the biosensors previously mentioned.